Picturing Culture: The Photography of Muttappan teyyam between 1920 and Today - Katja Müller
Three different appropriations of a 1928 photograph from South India allow insights into German anthropology in the 1920s, contemporary German museum practices, and present-day ritual forms in northern Kerala. Juxtaposing these readings as what Edwards named evidential strategies, power of representation, and re-experiencing demonstrates the possibilities and limits of visual representation. The article contributes to a Picturing Culture debate that considers entrenched visual economies of archived photographs, and opts for an understanding of different aspects of cultural knowledge transported through photographs.